EFFECT OF INTELLECTUAL CAPITAL AND INSTITUTIONAL OWNERSHIP ON THE FINANCIAL PERFORMANCE OF PHARMACEUTICAL COMPANIES IN INDONESIA - Ershazkiya Raudlatishafa; Erna Sulistyowati (Nurul Jadid University, 2025)
This study's primary goal is to investigate how institutional ownership and intellectual capital affect the financial performance of pharmaceutical businesses that are listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. In order to evaluate the association between the variables, this study uses a quantitative approach that starts with descriptive statistical analysis and ends with panel data regression. Purposive sampling was used to choose ten pharmaceutical sub-sector enterprises from the population, which is made up of businesses in the healthcare industry. The firms' yearly financial reports, which were retrieved from the official IDX website, provided secondary data. The Fixed Effect Model (FEM) strategy was selected based on the outcomes of model testing. The results show that institutional ownership and intellectual capital have no discernible impact on pharmaceutical businesses' financial success. This implies that institutional ownership and intellectual capital have not yet reached their full potential in improving business performance.